PALIVIZUMAB: NEW CAPABILITIES TO PREVENT SEVERE FORMS OF THE RESPIRATORY SYNCYTIAL VIRAL INFECTION IN CHILDREN - T.V. Kulichenko (Union of pediatricians of Russia, 2010)
Most bronchiolitis cases and viral pneumonias in young children are caused by respiratory syncytial viral (RSV) infection. Children with chronic diseases of lungs, congenital heart defects, pre-mature infants are at high risk of severe type of this infection. Hospitalization and mortality rates in these children are almost several times higher than originally health children. The article illustrates issues relating to the immunization prevention for severe forms of RSV infections in risk group children. The article discusses efficacy and safety of palivizumab, a RSV monoclonal antibodies medication. Key words: respiratory syncytial virus, respiratory infections, children, bronchiolitis, immunoprophylaxis, palivizumat, preterm infants, bronchopulmonary dysplasia, congenital heart defects. (Pediatric Pharmacology. - 2010; 7(4):40-47)